Description of six new species forming the sumbana species group of the genus Nemophora Hoffmannsegg (Lepidoptera, Adelidae) from the Lesser Sunda Islands in Indonesia - Kozlov, Mikhail V. (Zootaxa, 2024)
In this study six new species of the genus Nemophora Hoffmannsegg, 1798, are described from the Lesser Sunda Islands (Bali, Sumbawa, Sumba, and Timor) in Indonesia. These species (N. sumbana Kozlov, sp. nov., N. timorella Kozlov, sp. nov., N. umbronitidella Kozlov, sp. nov., N. wegneri Kozlov, sp. nov., N. longipeniculella Kozlov, sp. nov., and N. brevipeniculella Kozlov, sp. nov.) constitute a monophyletic group, characterized by a Λ-shaped yellow marking on the forewing, with the dorsal section of the distal leg of this marking extending along the outer wing margin.